William Shakespeare's Hamlet - Dunn, Ben; Shakespeare, William 1564-1616. (Edina, Minn. : Magic Wagon, 2009)
Retells, in comic book format, Shakespeare's play about a prince of Denmark who seeks revenge for his father's murder.
Keywords: Shakespeare, William -- 1564-1616; Graphic novels; Hamlet (Legendary character); Graphic novels